Challenges and Opportunities for Teacher Leaders in Public Schools - Tarraya, Hilger Ojos (ASEAN Journal of Educational Research and Technology, 2023)
This study explores the challenges encountered and emerging opportunities for teacher leaders in public schools. It employed the qualitative method of research, specifically phenomenological investigation. There are five participants, determined through purposive sampling. Thematic analysis was utilized in interpreting and analyzing data. Results of the study revealed the following challenges encountered by the teacher leaders: (1) Difficulty in managing time and harmonizing classroom and other functions/ roles; (2) The existence of "crab bucket culture" and isolation; (3) Lack of incentives or recognition for engaging in leadership activities; (4) Lack of leadership training and inadequate support and resources to carry out leadership functions; and (5) Uncertain opportunities for promotion of teacher leaders. The participants see teacher leadership as an opportunity to contribute to the school’s success. More than taking charge, they consider their designations as being the voice of teachers in decision-making, an opportunity for personal and professional development, and motivation to perform better. Many teacher leaders spend their time as assistants in administration and management rather than utilizing their instructional expertise to improve teaching and learning. Therefore, teacher leaders need support to overcome challenges.